Peran Orang Tua terhadap Penggunaan Gadget pada Anak Usia Dini Generasi Alpha - Mita Lestari Mita; RR. Deni Widjayatri (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The alpha generation is children born between 2011-2025. Alpha generation children are very familiar with digital technology as if their lives cannot be separated from the internet or gadgets. Therefore, with the development of increasingly sophisticated and increasingly rapid technology, early childhood requires good care, supervision, and assistance from their parents while using gadgets. The purpose of this study was to find out how parents' role in using gadgets in the early childhood alpha generation. This research uses a literature study method from scientific articles, journals, books, and others previously conducted to answer this research. This study showed that parents are very important in children using their gadgets. For example, parents must accompany children when playing with their gadgets, maintain good communication withchildren, manage the time they use gadgets for children every day, and parents can use parental control applications to monitor children when using the internet. The alpha generation is children born between 2011-2025. Alpha generation children are very familiar with digital technology as if their lives cannot be separated from the internet or gadgets. Therefore, with the development of increasingly sophisticated and increasingly rapid technology, early childhood requires good care, supervision, and assistance from their parents while using gadgets. The purpose of this study was to find out how parents' role in using gadgets in the early childhood alpha generation. This research uses a literature study method from scientific articles, journals, books, and others previously conducted to answer this research. This study showed that parents are very important in children using their gadgets. For example, parents must accompany children when playing with their gadgets, maintain good communication with children, manage the time they use gadgets for children every day, and parents can use parental control applications to monitor children when using theinternet.